Improving Critical Thinking Skills by Using the Project-Based Learning (PjBL) Model on Heat Transfer and Influence on Fifth Grade Students - Syahfitriani Br Ginting; Bernadetha Rizki Kaize; Herrio Tekdi Nainggolan; Ratna Purwanty (Universitas Pendidikan Ganesha, 2026)
Many students tend to be passive, less able to ask in-depth questions, and have difficulty analyzing and concluding information, especially in science learning that demands conceptual understanding and high-level thinking skills. This study aims to improve fifth-grade students' critical thinking skills by applying the PjBL model. The method used is CAR, with two cycles: planning, implementation, observation, and reflection. The research subjects were 25 fifth-grade elementary school students. Data collection techniques through observation, tests, and documentation with research instruments in the form of observation sheets and critical thinking evaluation questions. Data obtained from the test results were analyzed quantitatively using the Minimum Completion Criteria (KKM). The results of the study showed that the PjBL model gradually improved students' critical thinking skills, from an average of 49.28% and 44% completeness in cycle I to an average of 81.81% and 88% completeness in cycle II. This increase was evident in students' participation in discussions, their ability to formulate problems, and their ability to convey solutions logically and in a structured manner. Thus, the PjBL Model has been proven to improve critical thinking skills in the material on heat transfer and influence among fifth-grade students.